Reworking qualitative data - Heaton, Janet (Online access: SAGE SAGE Research Methods Core., 2004)
Comprehensive and invaluable introduction to this growing field of social research and will be a useful aid to academics, researchers and postgraduate students across the social sciences, but particularly in sociology and anthropology.